METODE PENDIDIKAN KEMANDIRIAN DI SEKOLAH ALAM BANYU BELIK - Kartikasari, Noviana (Jurnal Tawadhu, 2019)
Education is essentially a process of developing physical and spiritual potential, personality, and other aspects in the individual that are developed never stop and continue. While independence is the ability to control or regulate thoughts, feelings, and actions independently and try to overcome feelings of shame and doubt. In this case, independence education emphasizes the emotional state of a person not to depend on other people, is able to use his intellect in overcoming various problems, and is able to perform procedures for skills to interact and interact with others. The independence education applied in the Banyu Belik Nature School is done in 5 ways, namely: (1) exemplary method; (2) habituation methods; (3) educating with stories and advice; (4) gift giving method; and (5) disciplinary methods. The hope, from here, Banyu Belik Nature School is able to give birth to smart and superior generations and have mature skills and independence as a provision to realize a person of integrity for the sake of the nation, state and religion in the future.